Fungal Planet description sheets: 214-280 - P. W. Crous (2018)
Novel species of microfungi described in the present study include the following from South Africa: Cercosporella dolichandrae from Dolichandra unguiscati, Seiridium podocarpi from Podocarpus latifolius, Pseudocercospora parapseudarthriae from Pseudarthria hookeri, Neodevriesia coryneliae from Corynelia uberata on leaves of Afrocarpus falcatus, Ramichloridium eucleae from Euclea undulata and Stachybotrys aloeticola from Aloe sp. (South Africa), as novel member of the Stachybotriaceae fam. nov. Several species were also described from Zambia, and these include Chaetomella zambiensis on unknown Fabaceae, Schizoparme pseudogranati from Terminalia stuhlmannii, Diaporthe isoberliniae from Isoberlinia angolensis, Peyronellaea combreti from Combretum mossambiciensis, Zasmidium rothmanniae and Phaeococcomyces rothmanniae from Rothmannia engleriana, Diaporthe vangueriae from Vangueria infausta and Diaporthe parapterocarpi from Pterocarpus brenanii. Novel species from the Netherlands include: Stagonospora trichophoricola, Keissleriella trichophoricola and Dinemasporium trichophoricola from Trichophorum cespitosum, Phaeosphaeria poae, Keissleriella poagena, Phaeosphaeria poagena, Parastagonospora poagena and Pyrenochaetopsis poae from Poa sp., Septoriella oudemansii from Phragmites australis and Dendryphion europaeum from Hedera helix (Germany) and Heracleum sphondylium (the Netherlands). Novel species from Australia include: Anungitea eucalyptorum from Eucalyptus leaf litter, Beltraniopsis neolitseae and Acrodontium neolitseae from Neolitsea australiensis, Beltraniella endiandrae from Endiandra introrsa, Phaeophleospora parsoniae from Parsonia straminea, Penicillifer martinii from Cynodon dactylon, Ochroconis macrozamiae from Macrozamia leaf litter, Triposporium cycadicola, Circinotrichum cycadis, Cladosporium cycadicola and Acrocalymma cycadis from Cycas spp. Furthermore, Vermiculariopsiella dichapetali is described from Dichapetalum rhodesicum (Botswana), Marasmius vladimirii from leaf litter (India), Ophiognomonia acadiensis from Picea rubens (Canada), Setophoma vernoniae from Vernonia polyanthes and Penicillium restingae from soil (Brazil), Pseudolachnella guaviyunis from Myrcianthes pungens (Uruguay) and Pseudocercospora neriicola from Nerium oleander (Italy). Novelties from Spain include: Dendryphiella eucalyptorum from Eucalyptus globulus, Conioscypha minutispora from dead wood, Diplogelasinospora moalensis and Pseudoneurospora canariensis from soil and Inocybe lanatopurpurea from reforested woodland of Pinus spp. Novelties from France include: Kellermania triseptata from Agave angustifolia, Zetiasplozna acaciae from Acacia melanoxylon, Pyrenochaeta pinicola from Pinus sp. and Pseudonectria rusci from Ruscus aculeatus. New species from China include: Dematiocladium celtidicola from Celtis bungeana, Beltrania pseudorhombica, Chaetopsina beijingensis and Toxicocladosporium pini from Pinus spp. and Setophaeosphaeria badalingensis from Hemerocallis fulva. Novel genera of Ascomycetes include Alfaria from Cyperus esculentus (Spain), Rinaldiella from a contaminated human lesion (Georgia), Hyalocladosporiella from Tectona grandis (Brazil), Pseudoacremonium from Saccharum spontaneum and Melnikomyces from leaf litter (Vietnam), Annellosympodiella from Juniperus procera (Ethiopia), Neoceratosperma from Eucalyptus leaves (Thailand), Ramopenidiella from Cycas calcicola (Australia), Cephalotrichiella from air in the Netherlands, Neocamarosporium from Mesembryanthemum sp. and Acervuloseptoria from Ziziphus mucronata (South Africa) and Setophaeosphaeria from Hemerocallis fulva (China). Several novel combinations are also introduced, namely for Phaeosphaeria setosa as Setophaeosphaeria setosa, Phoma heteroderae as Peyronellaea heteroderae and Phyllosticta maydis as Peyronellaea maydis. Morphological and culture characteristics along with ITS DNA barcodes are provided for all taxa. © 2014 Naturalis Biodiversity Center & Centraalbureau voor Schimmelcultures.